Optimalisasi manajemen risiko pasar modal syariah di era disrupsi ekonomi society 5.0 melalui pemanfaatan teknologi finansial di indonesia - Rivana, Rezza (Maliki Interdisciplinary Journal, 2025)
This study examines the impact of digital transformation driven by Society 5.0 on risk management in Indonesia’s Islamic capital market amidst the era of economic disruption. It emphasizes the importance of integrating financial technologies such as fintech, artificial intelligence (AI), big data, blockchain, and regulatory tools like RegTech and ShariahTech to enhance the effectiveness of risk identification, measurement, and mitigation. Furthermore, the article highlights the need to adapt risk management frameworks particularly Enterprise Risk Management (ERM) and implement a Cyber Risk Management Framework that aligns with Shariah principles and addresses emerging cyber risks. Supportive regulatory roles, infrastructure development, improved digital and Islamic financial literacy, and cross-sector collaboration are identified as key factors in ensuring sustainable and resilient growth of the Islamic capital market in the face of technological challenges. With these strategic measures, Indonesia holds the potential to emerge as a pioneering, innovative, and highly competitive global digital Islamic capital market.